Some Aspects of Traffic Analysis used for Internet Traffic Prediction - Rutka, G. (Elektronika ir Elektrotechnika, 2009)
An overview of ARMA models used for traffic prediction is presented. The prediction of time series plays a very important role fornetwork planning. For this reason we build the network prediction models using ARMA, ARIMA and seasonal ARMA (SARMA)model. Analyzing these models we can underline the significance of seasonal component detection. SARMA is the best predictionmodel for time series containing seasonal component. Ill. 4, bibl. 11 (in English; summaries in English, Russian and Lithuanian).